PENGARUH ROA, ROE, PER, DAN EPS PADA HARGA SAHAM PERBANKAN YANG TERDAFTAR DI BEI PERIODE 2022-2024 - Rifqotul Itsnainiyah; Riska Ayu Setiawati (CV. Denasya Smart Publisher, 2026)
This study aims to analyze the effect of Return on Assets (ROA), Return on Equity (ROE), Price Earnings Ratio (PER), and Earnings Per Share (EPS) regarding the equity values of financial institutions registered on the Indonesia Stock Exchange during the 2022-2024 timeframe. The aggregate group for this investigation comprised 47 financial corporations, of which 20 companies were selected as samples through a purposive sampling approach. The methodological approach applied included testing classical assumptions, followed by multiple linear regression modeling. The outcomes of the study suggest that ROE, PER, and EPS exert a considerable positive influence on equity values, whereas ROA demonstrates no substantial impact. In totality, the four predictor variables collectively exert a considerable influence on equity value. These results suggest that banks with strong equity performance, sound market valuation, and high earnings per share are more capable of attracting investors and driving an increase in stock prices. The contribution of this research lies in providing recent empirical evidence on the fundamental factors affecting stock prices in the Indonesian banking sector, serving as a valuable reference for investors and management in making investment decisions and developing strategies to enhance corporate performance.